Brain Permeable AMP-Activated Protein Kinase Activator R481 Raises Glycaemia by Autonomic Nervous System Activation and Amplifies the Counterregulatory Response to Hypoglycaemia in Rats - Cruz, Ana M.; Partridge, Katie M.; Malekizadeh, Yasaman; Vlachaki Walker, Julia M.; Weightman Potter, Paul G.; Pye, Katherine R.; Shaw, Simon J.; Ellacott, Kate L. J.; Beall, Craig (Frontiers in Endocrinology, 2021)
Aim: We evaluated the efficacy of a novel brain permeable “metformin-like” AMP-activated protein kinase activator, R481, in regulating glucose homeostasis. Materials and Methods: We used glucose sensing hypothalamic GT1-7 neuronal cells and pancreatic TC1.9 -cells to examine the effect of R481 on AMPK pathway activation and cellular metabolism. Glucose tolerance tests and hyperinsulinaemic-euglycaemic and hypoglycaemic clamps were used in Sprague-Dawley rats to assess insulin sensitivity and hypoglycaemia counterregulation, respectively. Results: In vitro, we demonstrate that R481 increased AMPK phosphorylation in GT1-7 and TC1.9 cells. In Sprague-Dawley rats, R481 increased peak glucose levels during a glucose tolerance test, without altering insulin levels or glucose clearance. The effect of R481 to raise peak glucose levels was attenuated by allosteric brain permeable AMPK inhibitor SBI-0206965. This effect was also completely abolished by blockade of the autonomic nervous system using hexamethonium. During hypoglycaemic clamp studies, R481 treated animals had a significantly lower glucose infusion rate compared to vehicle treated controls. Peak plasma glucagon levels were significantly higher in R481 treated rats with no change to plasma adrenaline levels. In vitro, R481 did not alter glucagon release from TC1.9 cells, but increased glycolysis. Conclusions: These data demonstrate that peripheral administration of the brain permeable “metformin-like” AMPK activator R481 increases blood glucose by activation of the autonomic nervous system and amplifies the glucagon response to hypoglycaemia in rats. Taken together, our data suggest that R481 amplifies the counterregulatory response to hypoglycaemia by a central rather than a direct effect on the pancreatic -cell. These data provide proof-of-concept that central AMPK could be a target for future drug development for prevention of hypoglycaemia in diabetes.